An evaluation of TraClus-DL as a diagnostic tool for road transportation supply in the South-African local planning context: a case study of the town of Stellenbosch - Ter Huurne, Dominique (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021